Health-related quality of life in southern Iranian rural women: a multivariate multilevel study - Ayatollahi SMT; Zare N; Dehesh T (Dove Medical Press, 2015)
Seyed Mohammad Taghi Ayatollahi, Najaf Zare, Tania Dehesh Department of Biostatistics, School of Medicine, Shiraz University of Medical Sciences, Shiraz, Iran Purpose: The evaluation of health-related quality of life (HRQOL) is increasingly growing to be of much significance. In an attempt to improve the agricultural conditions and to prevent the rural–urban migration, analyzing HRQOL in rural communities has gained significant governmental attention. The purpose of this study was initially to investigate rural women’s HRQOL, and then to assess the influence of some specific covariates on four domains of rural women’s HRQOL via multivariate analysis (MA) and multivariate multilevel analysis (MMA), and finally to compare the results. Methods: Out of 146 active health centers in villages around Shiraz, Iran, ten health centers were selected, using a multistage random sampling process. These ten health centers covered 18 villages. In this cross-sectional study, all women over the age of 15 in a sample of 1,128 rural residents were interviewed using a brief version of the World Health Organization HRQOL (the WHOQOL-BREF) questionnaire. Assessing the influence of some specific covariates on the four domains of rural women’s HRQOL was conducted by MA and MMA. Results: The average range for all four domain scores was between 12.53 and 14.27, which indicates that HRQOL for rural women is acceptable on the whole. The social relations domain and the environmental domain received the highest (14.3±2.5 SD) and the lowest (12.5±2.3 SD) scores respectively. Marital status did not indicate any significant effects on MA, but it presented an important influence on MMA. Furthermore, age and chronic diseases showed indifferent levels of significance in the two analytical methods. Conclusion: Rural women are in need of more heedfulness during their lives, especially about facilities and health. MMA is a more accurate procedure in exploring the important covariates in HRQOL. Keywords: Health-related quality of life, multivariate multilevel analysis, multivariate analysis, rural women